VD_FINDINFO HC / 2015 / 137 vom 21. November 2014 - VD Tribunal cantonal (2014)
VENTE, DÉFAUT CACHÉ, DÉFAUT DE LA CHOSE, GARANTIE EN RAISON DES DÉFAUTS DE LA CHOSE | 197 al. 1 CO, 197 al. 2 CO, 197 CO, 199 CO